IDENTIFIKASI KANDUNGAN FORMALIN DAN KORELASI PENGETAHUAN DENGAN SIKAP PEDAGANG IKAN ASIN DI PASAR BARU JUWANA - Permadi, Aef Permadi; Yuniarti, Tatty (Marinade, 2022)
Processing fish into salted fish is an ancient traditional way that is still widely done in various countries including Indonesia. Although salted fish is very popular with the public, public knowledge about salted fish that is good and safe to consume is still less, it was evidenced by the many circulating salted fish sold in the market containing formalin. The purpose of the study was to identify the formalin content in salted fish in the Pasar Baru, Juwana, Pati City, knowing the character of traders, and the correlation between knowledge and the behavior of salted fish traders. The research methods carried out are by survey method, formalin testing with test kit and Correlation test. The results showed that fish products sold in Pasar Baru Juwana Pati as much as 27.7% of salted fish samples positive for formalin. Types of salted fish products that contain formalin are rebon, teri nasi, sepat, cumi, juwi, kipas, petek, layur, and petek, Formalin levels are as low as 1.50 mg/kg and highest at 43.49 mg/kg. Characteristics of traders are traders generally aged 51-60 years; most (91.6%) women, more who attend elementary school – high school (58.3%), all married, the longest trading is 0 - 10 years, generally the cost needs to trade around Rp 100,000 – Rp 500,000 and daily income selling salted fish, around Rp. 100,000 – Rp 500,000. The results of the correlation test between the level of knowledge and the behavior of traders show a very strong relationship.